Sinulariaone A: a novel diterpenoid with a 13-membered carbocyclic skeleton from an octocoral Sinularia species. Issue 15 (3rd April 2023) - Tseng, Hsuan-Jung; Kuo, Liang-Mou; Tsai, Yu-Chi; Hu, Hao-Chun; Chen, Po-Jen; Chien, Su-Ying; Sheu, Jyh-Horng; Sung, Ping-Jyun
Abstract : Chemical composition screening of an octocoral identified as Sinularia species led to the isolation of a novel diterpenoid, sinulariaone A (1 ), featuring a 13-membered carbocyclic skeleton. Abstract : Chemical composition screening of an octocoral identified as Sinularia species led to the isolation of a novel diterpenoid, sinulariaone A (1 ), featuring a 13-membered carbocyclic skeleton. The structure of 1 was established by spectroscopic elucidation, computed calculation, and X-ray diffraction analysis. Moreover, a single-crystal X-ray diffraction analysis of chlorofurancembranoid B (2 ), obtained in our previous study from the same octocoral species, was reported for the first time to demonstrate the absolute configuration. Diterpenoid 1 showed cytotoxicity towards human promyelocytic leukemia HL-60 cells, with an IC50 value of 38.01 μM.